2022
DOI: 10.1369/00221554221101662
|View full text |Cite
|
Sign up to set email alerts
|

GLUT1, LDHA, and MCT4 Expression Is Deregulated in Cervical Cancer and Precursor Lesions

Abstract: Metabolic reprogramming is typical in cancerous cells and is required for proliferation and cellular survival. In addition, oncoproteins of high-risk human papillomavirus (HR-HPV) are involved in this process. This study evaluated the relationship between glucose transporter I (GLUT1), lactate dehydrogenase A (LDHA), and monocarboxylate transporter type 4 (MCT4) expression and cervical intraepithelial neoplasia (CIN) and invasive cervical carcinoma (ICC) with HR-HPV infection. The protein expression was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…[ 18 ] Found that SLC2A1 has abundant methylation sites and was associated with immunosuppression in colon cancer. High expression of SLC2A1 in high-grade CIN with high-risk human papillomavirus (HR-HPV) infection indicates a high risk of cervical cancer [ 19 ]. This study also confirms that SLC2A1 and CA2 are highly expressed, and that CUX1 is weakly expressed, in cervical cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Found that SLC2A1 has abundant methylation sites and was associated with immunosuppression in colon cancer. High expression of SLC2A1 in high-grade CIN with high-risk human papillomavirus (HR-HPV) infection indicates a high risk of cervical cancer [ 19 ]. This study also confirms that SLC2A1 and CA2 are highly expressed, and that CUX1 is weakly expressed, in cervical cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are known to code for proteins involved in processes such as metabolic reprogramming [ 9 , 22 ], angiogenesis [ 28 ], cell migration, invasion, and metastasis [ 29 , 30 ]. High expression of GLUT1, LDHA, and MCT4 proteins has been observed in biopsies from patients with invasive cervical cancer [ 31 ]. Additionally, LDHA inhibition has resulted in cell cycle inhibition and apoptosis in nasopharyngeal carcinoma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…LDHA is a gene encoding a key glycolytic enzyme ( Tang et al, 2022 ). Reyna-Hernández et al found increased expression of LDAH in invasive cervical cancer ( Reyna-Hernández et al, 2022 ). Our research, which combined these six genes to create a predictive model, could help us better understand tumor cells.…”
Section: Discussionmentioning
confidence: 99%